Ensuring Fiscal Sustainability in G-7 Countries - Leigh, Daniel (IMF Working Papers; Working Paper, 2007)
Rising longevity, falling fertility rates, and the retirement of the baby boom generation will substantially raise age-related government spending in most advanced and many emerging market countries. This paper assesses the evolution of fiscal sustainability for each of the G-7 countries using two standard primary gap indicators. The estimated fiscal adjustment required to ensure long-run fiscal sustainability is substantial for all G-7 countries. In particular, ensuring fiscal sustainability would require an average improvement in the primary balance of about 4 percentage points of GDP. While the overall adjustment required to achieve long-run fiscal sustainability in G-7 countries is large, there are significant growth benefits to putting public finances on a sustainable footing in the near term versus delayed adjustment.